A few more notes to the interpretation of some hydronyms from the river basin of Slovak left tributaries of the river Morava - Závodný, Andrej (Geographical names in physical space, 2016)
In our paper we added motivations of some of the oldest names of rivers or creeks. The oldest hydronyms in the river basin of the Slovak left-sided tributary of Morava are from 13th century. Most of them are of old Slovak (Slavic) origin, but in addition to local people some such as other ethnic groups Germans, Hungarians and Croats began to settle there, which it had affected some toponymics of this region.